Simplified Visual Modelling Approach for Executable Software Generation - Binkis, M.; Blazauskas, T.; Bareisa, E. (Elektronika ir Elektrotechnika, 2011)
The idea of visual executable model was one of the goals, raised by model driven engineering. Emerging software developmenttechnologies and new standards have provided the base ground for the concept to be realized in practice - SCRALL and fUML are oneof the examples. Existing modelling methods are either too complex and not visual enough, or still aren’t sufficient enough to depictrequired information for a complete executable model. We are presenting a new modelling approach, consisting of UML class diagramsand flow diagrams, capable of conveying enough information for an executable model, while retaining the model fairly visual andcomprehendible, compared to the competing solutions. Ill. 14, bibl. 10, tabl. 14 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.613